2014
DOI: 10.1177/1468087414561275
|View full text |Cite
|
Sign up to set email alerts
|

Application of jet propellant-8 to premixed charge ignition combustion in a single-cylinder diesel engine

Abstract: The aviation fuel, jet propellant-8, was applied to premixed charge ignition combustion as well as conventional combustion in a single-cylinder diesel engine and was compared with diesel fuel. The engine performance and emissions were tested with and without exhaust gas recirculation under two operating conditions. The liquid- and vapor-phase penetration of diesel fuel and jet propellant-8 were also compared by Mie-scattering and Schlieren method under evaporating conditions using a constant-volume chamber. It… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
48
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(49 citation statements)
references
References 29 publications
1
48
0
Order By: Relevance
“…53 From Figures 5(c), 6(a), and 7, it can be observed that kerosene and diesel sprays are generally quite similar except for some minor differences. 49,53,81 Due to kerosene’s lower density and higher volatility as compared to diesel, kerosene’s liquid penetration was seen to be shorter than diesel. 53,81 However, this difference was less obvious when the ambient density was higher as spray behavior became dominated by ambient condition.…”
Section: Experimental Studies Of Kerosene Spray and Combustion In Cvccsmentioning
confidence: 81%
See 3 more Smart Citations
“…53 From Figures 5(c), 6(a), and 7, it can be observed that kerosene and diesel sprays are generally quite similar except for some minor differences. 49,53,81 Due to kerosene’s lower density and higher volatility as compared to diesel, kerosene’s liquid penetration was seen to be shorter than diesel. 53,81 However, this difference was less obvious when the ambient density was higher as spray behavior became dominated by ambient condition.…”
Section: Experimental Studies Of Kerosene Spray and Combustion In Cvccsmentioning
confidence: 81%
“…The pioneering work was done by the group from SNL which consisted of Pickett and Hoogterp 81 as well as Kook and Pickett. 49,87,88 Following their lead, others who had contributed to this area were Lee and Bae, 5 Park et al, 53 Jing et al, 89 Kang et al, 66 Song et al, 90 and the authors’ research group. 91,92…”
Section: Experimental Studies Of Kerosene Spray and Combustion In Cvccsmentioning
confidence: 99%
See 2 more Smart Citations
“…Selected papers include two papers related to fuel injection, 4,5 two papers on turbocharging 6,7 and seven papers on combustion. [8][9][10][11][12][13][14] With respect to the articles selected for the injection part, in the work of Watanabe et al, 4 the visualization of cavitation inside real-size nozzles is presented for different nozzle seats changing the sac volume, finding that vortex flow within the sac affects the spray characteristics at the beginning of needle lift. 3 The visualization of the cavitation phase in real-size nozzles has been a very active research work as could be observed from the work of Reid et al 15 To pass from fuel injection system to combustion, the most common situation is to use one-dimensional code for injection modelling 16,17 or to make use of zero dimensional codes for the prediction of spray characteristics.…”
mentioning
confidence: 99%